Síndrome metabólica, perfil nutricional e risco cardiovascular - Lima, Viviane do Nascimento (2014)
One of Overweight consequences is the development of metabolic syndrome which is characterized as a complex disorder represented by a set of cardiovascular risk factors related to central fat distribution and insulin resistance. Bariatric surgery is currently considered the most effective treatment for morbid obesity (BMI ≥40,0 kg / m2), but the indication for surgery should take into consideration, in addition to BMI, the association of obesity with comorbidities in individuals in whom failure occurred in the clinical treatment for weight loss and presenting psychological conditions for the procedure. This thesis is divided in two studies. The first study, entitled Metabolic syndrome in Brazilian adult women: a systematic review and the second paper entitled Metabolic syndrome, nutritional status and cardiovascular risk. The first study deals with a systematic review performed in electronic databases PubMed and Scielo taking into account the last 10 years. 28 articles selected for reading and systematization. As a result, the prevalence of MS was identified high. In individuals with polycystic ovary syndrome (PCOS) higher prevalence was 44%. The criteria that make up the metabolic syndrome in this group, the HDL cholesterol was the most prevalent (67.6%) and fasting plasma glucose the lowest prevalence (4.3%). An interesting finding was the association of MS with PCOS, is important to conduct further studies to investigate this association. The purpose of the second study was to evaluate and compare the late effect of weight loss determined by bariatric surgery on the nutritional status and cardiovascular risk of individuals according to the Framingham score. This is an observational, longitudinal, prospective analytical of a sample of patients with obesity and bariatric surgery indication, inserted in the Bariatric Surgery Program, University Hospital Professor Alberto Antunes (HUPAA), the Federal University of Alagoas. It was observed that bariatric surgery was able to reduce a significant degree body weight, however, the loss was not enough to put all investigated within the normal range for BMI (BMI <25 kg / m2). Blood pressure was the variable that bore the brunt of positive effect of surgery. Of the 27 patients 16 were diagnosed hypertensive and after surgery only one patient remained hypertensive. When analyzed the variables that determine cardiovascular risk in 10 years using the Framingham score is consisted that before surgery the sum of the points was 7.8 ± 5.7, with this group the risk of cardiovascular events (heart attack or death from coronary artery disease) in 10 years of 2.6 ± 2.7%; two years after surgery, the sum of the points was 1.4 ± 6.0, which reduced cardiovascular risk to 1.5 ± 1.2%.